Biological Role of Aldo–Keto Reductases in Retinoic Acid Biosynthesis and Signaling - Ruiz, F. Xavier; Porté, Sergio; Parés, Xavier; Farrés, Jaume (Frontiers in Pharmacology, 2012)
Several aldo-keto reductase (AKR) enzymes from subfamilies 1B and 1C show retinaldehyde reductase activity, having low Km and kcat values. Only AKR1B10 and 1B12, with all-trans-retinaldehyde, and AKR1C3, with 9-cis-retinaldehyde, display high catalytic efficiency. Major structural determinants for retinaldehyde isomer specificity are located in the external loops (A and C for AKR1B10, and B for AKR1C3), as assessed by site-directed mutagenesis and molecular dynamics. Cellular models have shown that AKR1B and 1C enzymes are well suited to work in vivo as retinaldehyde reductases and to regulate retinoic acid (RA) biosynthesis at hormone pre-receptor level. An additional physiological role for the retinaldehyde reductase activity of these enzymes, consistent with their tissue localization, is their participation in β-carotene absorption. Retinaldehyde metabolism may be subjected to subcellular compartmentalization, based on enzyme localization. While retinaldehyde oxidation to RA takes place in the cytosol, reduction to retinol could take place in the cytosol by AKRs or in the membranes of endoplasmic reticulum by microsomal retinaldehyde reductases. Upregulation of some AKR1 enzymes in different cancer types may be linked to their induction by oxidative stress and to their participation in different signaling pathways related to cell proliferation. AKR1B10 and AKR1C3, through their retinaldehyde reductase activity, trigger a decrease in the RA biosynthesis flow, resulting in RA deprivation and consequently lower differentiation, with an increased cancer risk in target tissues. Rational design of selective AKR inhibitors could lead to development of novel drugs for cancer treatment as well as reduction of chemotherapeutic drug resistance.